CoDNaS 2.0: a comprehensive database of protein conformational diversity in the native state - Monzón, Alexander (2016)
CoDNaS (conformational diversity of the native state) is a protein conformational diversitydatabase. Conformational diversity describes structural differences between conformersthat define the native state of proteins. It is a key concept to understand proteinfunction and biological processes related to protein functions. CoDNaS offers a well curateddatabase that is experimentally driven, thoroughly linked, and annotated. CoDNaS facilitatesthe extraction of key information on small structural differences based on proteinmovements. CoDNaS enables users to easily relate the degree of conformational diversitywith physical, chemical and biological properties derived from experiments on proteinstructure and biological characteristics. The new version of CoDNaS includes 70%of all available protein structures, and new tools have been added that run sequencesearches, display structural flexibility profiles and allow users to browse the database fordifferent structural classes. These tools facilitate the exploration of protein conformationaldiversity and its role in protein function.